2019
DOI: 10.1371/journal.pone.0211968
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel predictive miRNA/target gene pathways for colorectal cancer distance metastasis to the liver using a bioinformatic approach

Abstract: Background Liver metastases are the major cause of colorectal cancer (CRC)-related deaths. However, there is no reliable clinical predictor for CRC progression to liver metastasis. In this study, we investigated possible predictors (miRNAs and biomarkers) for clinical application. Methodology The Gene Expression Omnibus (GEO) datasets GSE49355, GSE41258 and GSE81558 for genes and GSE54088 and GSE56350 for miRNAs were used to identify common differentially expressed genes (DEGs) and miRNAs between primary CRC t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Previous studies have revealed that miR-576-5p plays an important role in CRC metastases. Compared with primary CRC tumors, miR-576-5p is significantly downregulated in the most common liver-metastatic carcinomas and is expressed at high levels in rare brain-metastatic carcinomas 14 , 15 . However, there is little research on the mechanism of miR-576-5p in CRC, which is worthy of further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that miR-576-5p plays an important role in CRC metastases. Compared with primary CRC tumors, miR-576-5p is significantly downregulated in the most common liver-metastatic carcinomas and is expressed at high levels in rare brain-metastatic carcinomas 14 , 15 . However, there is little research on the mechanism of miR-576-5p in CRC, which is worthy of further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, miRNAs were also considered as non-functional RNA, but more and more studies have shown that miRNAs are involved in various biological functions of cells (Tarallo et al 2019;Xu et al 2020;Vignard et al 2020). Many studies have shown that miRNA-576-5p plays an important role in a variety of cancers, such as esophageal cancer (Zhang et al 2019), colorectal cancer (Makondi et al 2019) and melanoma (Kordaß et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Rarely a single miRNA is recognized as a specific biomarker. Recently, miR-576-5p and miR-20a have been identified as individual classifiers in CRC patients who may develop liver metastases, but the combination of the two, or better yet six, miRNAs has offered a far more effective model [13]. The mechanisms that control the progression of CRC may depend on the deregulation of multiple miRNAs resulting in complex dysfunction of cellular molecular networks.…”
Section: Discussionmentioning
confidence: 99%